Analyzing the Behavioral Intention Factors in Using Zakat-Based Crowdfunding Platform in Indonesia - Sulaeman Sulaeman; Sri Yayu Ninglasari (International Journal of Zakat, 2020)
This study aims to examine the behavioral intention of the Muslim crowd funders to use the Zakat-based crowdfunding platform model by adopting the Unified Theory of Acceptance and Use of Technology (UTAUT) Model. The online platform, as an intermediary between Muslim crowd funders and MSMEs, provides financing services for MSMEs to fight any situation/pandemic like COVID-19 nowadays. This study used the primary data collected by using the online survey questionnaires, and then the analysis is conducted using partial least squares (PLS) regression. The empirical study shows that all the variables except for facilitating conditions have a significant positive effect on Muslim crowd funders' intention to use the Zakat-based crowdfunding platform model. The present study will help the government and policymakers to plan appropriate intervention strategies to minimize the adverse impact of the COVID-19 pandemic on MSMEs in Indonesia. Furthermore, the study will contribute to the existing literature, especially on the factors influencing the adoption of the Zakat-based crowdfunding platform model.